Acute Acalculous Cholecystitis Due to a Primary Epstein Barr Virus Infection in a Pediatric Patient - Carlos Leganés Villanueva; Ilaria Goruppi; Nuria Brun Lozano; Federica Bianchi; María Quinteiro González; Susana Boronat Guerrero (MDPI AG, 2021)
Epstein-Barr virus (EBV) is estimated to infect more than 98% of adults worldwide and is one of the most common human viruses. Acute acalculous cholecystitis (AAC) of the gallbladder is an atypical complication of infectious mononucleosis caused by EBV. Conservative management has been described in the context of AAC caused by EBV. A surgical approach must be considered in the case of acute complications such as perforation or gallbladder gangrene. We present the case of a 10-year-old female patient with AAC due to infectious mononucleosis syndrome caused by primary EBV infection.